Krypton gas separation compound as well as preparation method and application thereof
By using cadmium ionic metal organic frame material to adsorb Krypton gas at room temperature, the problems of expensive and harsh conditions in the prior art Krypton gas separation equipment are solved, and efficient and safe Krypton gas separation and purification effects are achieved.
Patent Information
- Application Number
- CN202310571128.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-20
- Publication Date
- 2024-12-24
AI Technical Summary
The prior art equipment is expensive and harsh when separating krypton gas, making it difficult to achieve efficient capture and re-release at room temperature.
Using cadmium ionic metal organic framework materials based on 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane and 2-amino-terephthalic acid, through intermolecular action Adsorb krypton gas to form Cd(ATPA(4,4'-BD)) compounds, which are used for the adsorption and separation of gases.
It achieves efficient, safe and economical separation and purification of Krypton gas at room temperature, has good thermal stability and high yield, and is suitable for the treatment of industrial waste gas and nuclear waste gas.
Smart Images

Figure CN119176823A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of gas adsorption metal organic framework compounds, and in particular relates to a krypton gas separation compound and a preparation method and application thereof. Background Art
[0002] Krypton gas is an inert gas and is indispensable in medicine, industry and scientific research. There is abundant krypton gas in the atmosphere. 3 1mL 3 krypton, but its separation is more difficult. At present, most of the following five methods are used: 1. Air separation method: compress and expand the air to cool it, and then remove the moisture and impurities in the air. The air is cooled and liquefied by heat exchange, and the air is distilled and separated. The cold capacity of the low-temperature product is recovered and compressed; 2. Synthetic ammonia tail gas separation method: the synthetic ammonia tail gas argon extraction process produces a mixture of krypton and xenon as by-products, which can be distilled, washed, deoxygenated, adsorbed and desorbed to produce 99% krypton gas; 3. Nuclear reactor waste gas separation method: Comprehensive utilization of radioactive Kr85 in the cracking waste gas of the nuclear reactor; 4. Freon solvent absorption method is also used in industry; 5. Diverting liquid air method: distilling liquid air from air. The above methods all have the disadvantages of expensive equipment and harsh conditions. Therefore, if krypton gas can be captured and released at room temperature, it has become a key issue. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies of the prior art and provide a krypton gas separation compound and a preparation method and application thereof, specifically adopting the following technical solutions: According to a first aspect of the present invention, a krypton gas separation compound is provided, whose molecular formula is Cd(ATPA(4,4'-BD)); whose asymmetric unit comprises a crystallographically independent divalent Cd ion, 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and a 2-amino-terephthalic acid anion.
[0004] The krypton gas separation compound prepared by the present invention is a metal organic framework material compound based on 1,2-di[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane and 2-amino-terephthalic acid double ligands to construct cadmium ions, and is a functional material that relies on intermolecular forces to adsorb krypton gas. The material is crystallized in the monoclinic system, and the space group is P21 / c. In the coordination environment, the divalent Cd presents a pentagonal bipyramidal coordination geometry and is connected to form a secondary structure, the vertices are provided by two nitrogen atoms of 1,2-di[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane to form Cd-N, and the basal plane is composed of four oxygen atoms of four 2-aminoterephthalic acid anions to form Cd-O bonds; the distance of the Cd-O bond is 2.267-2.286 Å, and the distance of the Cd-N bond is 2.325 Å. 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane ligand can undergo photochromic cyclization reaction in the free state; due to the asymmetry of the secondary structure and the length of 2-amino-terephthalic acid inside the crystal, it forms a cis coplanar structure and twists to form a rigid structure. It has better performance in synthesis, yield, purity, thermal stability and adsorption separation function.
[0005] Preferably, the coordination mode of the 2-amino-terephthalate anion is bidentate bridging μ2-ƞ1:ƞ1. 2-amino-terephthalic acid is a linear bi-group rigid ligand with small amino side chains, small steric hindrance, and good bridging effect of carboxylate. Transition metals have strong coordination ability with the carboxylate of 2-amino-terephthalic acid and can form complexes with various spatial structures, among which grid, linear, and trapezoidal are the main ones. Octahedral, honeycomb, and diamond types also exist according to the different secondary structures. The nitrogen atom of 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane has strong coordination ability and can coordinate with the plane formed by transition metals and terephthalic acid derivatives.
[0006] Preferably, the structure of 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane is arranged in a cis parallel conformation, and the distance between the two active carbon atoms is 4.089 Å. In Cd(ATPA(4,4'-BD)), due to the asymmetry of the secondary structure, the side chain groups and perfluorocyclopentane of 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane are twisted during the coordination process. Therefore, 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane forms a cis coplanar asymmetric structure inside the crystal. Although the distance between the two active carbon atoms is 4.089<4.2 Å, the optical activity is still lost.
[0007] Preferably, the krypton gas separation compound is a 3-node 5-c net connection network, and its topology symbol is {3^3.4^3.5^4}.
[0008] According to a second aspect of the present invention, there is also provided a method for preparing the above-mentioned krypton gas separation compound, comprising the following steps: 2-Amino-terephthalic acid, 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and Cd(NO3)2·4H2O were added to a mixed solution containing dimethylformamide, methanol and H2O, heated at 80°C for 72h, filtered and washed to obtain a krypton gas separation compound.
[0009] The present invention adopts a rigid metal organic framework material formed by 1,2-di[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane for the first time, and applies the rigid metal organic framework material as a stationary phase to the gas adsorption and separation process, especially rare gases and gas molecules with relatively concentrated electron density. The preparation method does not require the use of expensive gas separation equipment, the separation conditions are simple and convenient, and pure and stable gas can be obtained at the same time, and the gas yield is high. It is a safe and efficient preparation method.
[0010] Preferably, the molar ratio of 2-amino-terephthalic acid, 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane and Cd(NO3)2·4H2O is 1:1:1. The synthesized metal organic framework material is designed by adopting the self-assembly strategy of synthesizing metal organic framework materials. 2-amino-terephthalic acid combines with Cd (II) to form a plane, so the ratio of the two is 1:1. 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane has two coordination sites and can connect two metal sites, so the ratio of the two is 1:1. Therefore, when the ratio of the three substances is 1:1:1, they can be combined into crystals.
[0011] Preferably, in the mixed solution, the volume ratio of dimethylformamide, methanol, and H2O is 3:1:1. The polarity of the mixed solution will affect the speed and size of crystallization. When methanol or water is excessive, the polarity of the solution will increase, which will accelerate the crystallization process, and more crystal nuclei will be formed in the solution, which is not conducive to the growth of crystals; when dimethylformamide is excessive in the solution, the polarity of the solution increases slowly, and the same reaction conditions do not have much effect on the growth of crystal nuclei. In order to save drugs, the volume ratio of dimethylformamide, methanol, and H2O is selected to be 3:1:1.
[0012] Preferably, the washing step is to repeatedly rinse with dimethylformamide and ethanol for 3 times.
[0013] According to the third aspect of the present invention, there is also provided the use of the above-mentioned krypton gas separation compound in separating and purifying industrial waste gas and nuclear waste gas rich in krypton gas.
[0014] The beneficial effects of the present invention are as follows: the present invention adopts for the first time a rigid metal organic framework material formed by 1,2-di[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane, and applies the rigid metal organic framework material as a stationary phase to the gas adsorption and separation process. The preparation method of the present invention does not require the use of expensive gas separation equipment, and the separation conditions are simple and convenient. At the same time, pure and stable gas can be obtained with a high gas yield. The krypton gas separation compound prepared by the present invention has a high yield and high purity, and has good thermal stability, adsorption and separation performance, and can be widely used in the separation and purification of industrial waste gas and nuclear waste gas rich in krypton gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Shown is a synthetic route for the ligand 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane; Figure 2 Shown is the synthesis route of Cd(ATPA(4,4'-BD)) crystalline material; Figure 3 Shown is the thermogravimetric diagram of Cd(ATPA(4,4'-BD)) prepared in Example 1; Figure 4 Shown is the infrared spectrum of Cd(ATPA(4,4'-BD)) prepared in Example 1; Figure 5 Shown is the X-ray diffraction pattern of Cd(ATPA(4,4'-BD)) prepared in Example 1; Figure 6 Shown is the nitrogen gas adsorption diagram of Cd(ATPA(4,4'-BD)) prepared in Example 1; Figure 7 Shown is the krypton gas adsorption diagram of Cd(ATPA(4,4'-BD)) prepared in Example 1; Figure 8 Shown is the adsorption diagram of six common gases by Cd(ATPA(4,4'-BD)) prepared in Example 1; Fig. 9 Shown is the penetration diagram of Cd(ATPA(4,4'-BD)) prepared in Example 1 in low concentration krypton gas; Fig.10 Shown is a scanning electron micrograph of Cd(ATPA(4,4'-BD)) prepared in Example 1. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments and drawings to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.
[0017] Example 1 A krypton gas separation compound Cd (ATPA (4,4'-BD)), the preparation method of which comprises the following steps: (1) Synthesis of ligand 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane (synthetic route: Figure 1 shown): Weigh 2-methylthiophene (19.79 g, 201.9 mmol) accurately and place it in a 250 mL single-necked flask, add 150.0 mL glacial acetic acid and stir, slowly add NBS (71.88 g, 444.2 mmol) in an ice bath environment for about 2 h, keep reacting for 12 h after adding NBS, judge the progress of the reaction by thin layer chromatography, and add appropriate amount of water to stop the reaction after the reaction. Add 120.0 mL of dichloromethane and a large amount of water, extract 3 times until the water layer is colorless or light yellow and there is no white floc in the organic phase, combine the organic phases, wash with saturated brine, dry with anhydrous sodium sulfate, evaporate under reduced pressure, remove the solvent, and separate by silica gel column chromatography, the eluent is pure petroleum ether, the product 2 is a colorless or light yellow liquid (41.9 g, yield: 81.74%), the structural analysis of the target product is: 1 H NMR (400 MHz, DMSO- d 6 ) δ (ppm): 6.76 (s, 1H), 2.36 (s, 3H).
[0018] Accurately weigh 2-methyl-3,5-dibromothiophene (40.7 g, 160.3 mmol) and add it to a 250.0 mL three-necked flask. Add 150 mL of refined tetrahydrofuran liquid. In an argon atmosphere at a low temperature of -78 ºC, slowly add n-butyl lithium using a syringe for about 1 h, and keep it at -78 ℃ for 1 h. Dilute bromosilane liquid (24.93 mL, 164.0 mmol) with refined tetrahydrofuran liquid by more than two times, slowly add it to the three-necked flask through a separatory funnel or a syringe, observe the color of the reaction system, and determine the drop rate of the reaction raw materials. After the addition of bromosilane is completed, keep the reaction system for 12 h, judge the reaction progress by thin layer chromatography, and add an appropriate amount of clean water to stop the reaction after the reaction is completed. 120.0 mL of dichloromethane and a large amount of water were added, and the mixture was extracted three times until the water layer was colorless or light yellow and the organic phase had no white flocs. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to remove the solvent. The mixture was separated by silica gel column chromatography using pure petroleum ether as the eluent. The product 3 was a light yellow liquid (30.56 g, yield: 76.68%). The structural analysis of the target product is as follows: 1 H NMR (400 MHz, DMSO- d 6 ) δ (ppm): 6.95 (s, 1H), 2.40 (s, 3H), -0.02 (s, 9H).
[0019] Accurately weigh [1,2-bis[2-methyl-3-thienyl-5-silane]]perfluorocyclopentane (12.46 g, 50.3 mmol) and add it to a 250.0 mL three-necked flask. Add 150 mL of refined tetrahydrofuran liquid. In an argon atmosphere at a low temperature of -78 ºC, slowly add n-butyl lithium (22.1 mL, 55.3 mmol) using a syringe for about 1 h, and keep it at -78 ℃ for 1 h. Dilute the perfluorocyclopentene liquid (3.4 mL, 25.1 mmol) with refined tetrahydrofuran liquid by more than two times, slowly add it to the three-necked flask through a separatory funnel or a syringe, observe the color of the reaction system, and determine the drop rate of the reaction raw materials. After the perfluorocyclopentene is added, keep the reaction system for 12 h, judge the reaction progress by thin layer chromatography, and add an appropriate amount of clean water to stop the reaction after the reaction. 120.0 mL of dichloromethane and a large amount of water were added, and the mixture was extracted three times until the water layer was colorless or light yellow and the organic phase had no white flocs. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to remove the solvent and separated by silica gel column chromatography with pure petroleum ether as the eluent. The product 4 was a brown liquid. The brown liquid was kept at 60 °C for 6 h, and then quickly stored at low temperature for 12 h to obtain white or light yellow crystals (11.5 g, yield: 92.30%). The structural analysis of the target product is as follows: 1 HNMR (400 MHz, DMSO- d 6 ) δ (ppm): 7.02 (s, 2H), 2.43 (s, 6H), -0.03 (s, 18H).
[0020] Take [1,2-di[2-methyl-3-thienyl-5-bromo]]perfluorocyclopentane (14 g, 27.4 mmol) into a 250.0 mL single-necked flask, dissolve in 120.0 mL acetonitrile solution, slowly add NBS (10.9 g, 67.5 mmol) in an ice-water bath environment for about 1 h, and then keep the reaction for 12 h. The progress of the reaction was judged by thin layer chromatography. After the reaction was completed, an appropriate amount of water was added to stop the reaction. 120.0 mL of dichloromethane and a large amount of water were added, and extracted 3 times until the water layer was colorless or light yellow and there was no white flocculent in the organic phase. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, and evaporated under reduced pressure to remove the solvent. The product 5 was separated by silica gel column chromatography with pure petroleum ether as the eluent. The product 5 was a light yellow transparent solid (13.7 g, yield: 95.67%). The structural analysis of the target product is as follows: 1 H NMR (400 MHz, DMSO- d 6 ) δ(ppm): 7.2 (s, 2H), 2.35 (s, 6H).
[0021] The compound [1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane (1 g, 1.91 mmol), 4-pyridineboronic acid (0.516 g, 4.2 mmol) and triphenylphosphine palladium catalyst (0.05 g) were accurately weighed and dissolved in tetrahydrofuran or a mixture of ether and 20% sodium carbonate aqueous solution, with a volume ratio of about 1:1. Under argon protection, the temperature was slowly raised to 75 °C and condensed and refluxed for 12 h. The reaction progress was judged by thin layer chromatography. After the reaction was completed, an appropriate amount of clean water was added to stop the reaction. 120.0 mL of dichloromethane and a large amount of clean water were added, and the extraction was performed three times until the water layer was colorless or light yellow and there was no white flocculent in the organic phase. The organic phases were combined, washed with saturated brine, dried over anhydrous sodium sulfate, evaporated under reduced pressure, the solvent was removed, and separated by silica gel column chromatography with pure petroleum ether as the eluent. The product 6 was a blue powder (0.8 g, yield: 80.27%). The structural analysis of the target product is as follows: 1 H NMR (400 MHz, DMSO- d 6 ) δ (ppm): 8.75 (m, 4H), 8.01 (m, 4H), 7.06 (s, 2H), 2.36 (s, 6H).
[0022] (2) Preparation of Cd(ATPA(4,4'-BD)) crystal materials (synthetic route as follows Figure 2 shown): [1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane (10 mg, 0.019 mmol), 2-amino-terephthalic acid (3.5 mg, 0.019 mmol) and Cd(NO3)2·4H2O (5.9 mg, 0.019 mmol) were dispersed in 5.0 mL of dimethylformamide / methanol / H2O (v:v:v=3:1:1) solution, then sealed in a 25.0 mL polytetrafluoroethylene-lined autoclave and heated at 80 °C for 72 h. Brown colorless transparent block crystals were obtained by filtration and washed with dimethylformamide and ethanol three times, with a yield of 87.20%.
[0023] Example 2 In this example, crystal measurement is performed on the Cd(ATPA(4,4′-BD)) crystal material prepared in Example 1.
[0024] Test method: The diffractometer was used for measurement at room temperature using a Bruker SMART APEX II single crystal diffractometer and refined using the SHELX-2014 program and the full matrix least squares method. All non-hydrogen atoms were anisotropically refined. During the refinement process, the SQUEEZE program in PLATON was used to remove the disordered guest molecules.
[0025] Specific results such as Figure 2 (a) is the crystal and of the material obtained in Example 1, Figure 2 (b) is a topological diagram obtained in Example 1. Cd (ATPA (4,4'-BD)) belongs to the monoclinic P21 / c space group, and its asymmetric unit contains a crystallographically independent divalent Cd ion, a 1,2-di[2-methyl-3-thienyl-5-pyridine] perfluorocyclopentane and a 2-amino-terephthalic acid anion. In the coordination environment, the divalent Cd presents a pentagonal bipyramidal coordination geometry and is connected to form a secondary structure. The vertices are provided by two nitrogen atoms of 1,2-di[2-methyl-3-thienyl-5-pyridine] perfluorocyclopentane to form Cd-N, and the base plane is composed of four oxygen atoms of four 2-aminoterephthalic acid anions to form Cd-O bonds. The preparation method of the crystal is to use 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane, a 2-amino-terephthalic acid and cadmium nitrate tetrahydrate in a high temperature and high pressure reactor. The distance of the Cd-O bond is 2.267-2.286 Å, and the distance of the Cd-N bond is 2.325 Å. The coordination mode of the 2-amino-terephthalate anion is bidentate bridging μ2-ƞ1:ƞ1, and the structure of 1,2-bis[2-methyl-3-thienyl-5-pyridine]perfluorocyclopentane is arranged in a cis parallel conformation, and the distance between the two active carbon atoms is 4.089 Å. The secondary structure of the crystal material is a 3-node 5-c net connection network. In order to describe its structure more intuitively, its topological symbol is {3^3.4^3.5^4}. The nitrogen atom of 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane has a strong coordination ability and can coordinate with the plane formed by transition metals and terephthalic acid derivatives. In Cd(ATPA(4,4'-BD)), due to the asymmetry of the secondary structure, the side chain groups and perfluorocyclopentane of 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane are distorted during the coordination process. Therefore, 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane forms a cis-coplanar asymmetric structure inside the crystal. Although the distance between the two active carbon atoms is 4.089<4.2Å, it still loses its optical activity.
[0026] Example 3 In this example, the thermal stability of the Cd(ATPA(4,4′-BD)) crystal material prepared in Example 1 was tested.
[0027] Test method: The thermal stability of the sample was investigated by using an SDT Q600 V20.9 Build 20 thermal analyzer in an air atmosphere at a heating rate of 10°C / min from room temperature to 800°C.
[0028] like Figure 3 As shown in the figure, the thermogravimetric curve of Cd(ATPA(4,4'-BD)) shows a weight loss of 8.14% before 274.34 ℃, which is mainly due to the weight of free water molecules, methanol and DMF in the pores; a weight loss of 47.98% before 351.5 ℃, which is mainly due to the disintegration of the plane formed by ATPA and the dissociation of half of APTA; a weight loss of 83.42% before 559.34 ℃, which is mainly due to the total loss of 4,4'-BD and APTA, and finally decomposition into CdO. The crystal maintains the stability of the crystal structure at 274.34 ℃.
[0029] Example 4 In this example, infrared spectroscopy was performed on the Cd(ATPA(4,4'-BD)) crystal material prepared in Example 1.
[0030] Test method: Dry KBr pellets were used to record the wavelength range of 4000-400 cm-1 of perfluorodithienylethylene formic acid and Cd (ATPA(4,4'-BD)) on a Bruker Vertex-70 Fourier transform infrared spectrometer. -1 The infrared spectra of Cd(ATPA(4,4'-BD)), ATPA and 4,4'-BD were compared.
[0031] like Figure 4 As shown, at 1720 cm -1 and 2500 cm -1 -3000cm -1 It can be determined whether the derivative of terephthalic acid participates in the coordination and whether the ligand exists inside the crystal. The presence of amino groups can be determined by the double peaks at 3300 cm-1 and nearby. The experimental results of infrared spectroscopy are consistent with the description of the crystal structure.
[0032] Example 5 In this example, the Cd(ATPA(4,4′-BD)) crystal material prepared in Example 1 was subjected to an X-ray diffraction test.
[0033] Test Methods: Powder X-ray diffraction (PXRD) characterization was performed on a Shimadzu Lab Xrd-6100 X-ray diffractometer using Cu radiation in the 2θ range of 5 ºC-80 ºC at room temperature to determine the purity of the samples and whether the structure of the crystals has changed.
[0034] like Figure 5 As shown, the spectrum of the experimentally synthesized sample is in good agreement with the PXRD spectrum (blue) simulated from Mercury single crystal data, indicating that the synthesized crystalline Cd(ATPA(4,4'-BD)) has a high phase purity.
[0035] Example 6 In this example, a nitrogen gas adsorption experiment was performed on the Cd(ATPA(4,4′-BD)) crystal material prepared in Example 1.
[0036] Test method: Soak the sample in a methanol solution for three days, change the solution once a day, and place it in a 60°C oven for 8 hours to complete the activation of the sample. The activated sample enters the gas adsorption device.
[0037] Due to the regular pore size and huge specific surface area of metal organic framework materials, they have great potential in gas adsorption. At present, nitrogen adsorption is the main means and evaluation standard for measuring the adsorption properties of porous materials. Figure 6 The curve of nitrogen adsorption by Cd(ATPA(4,4'-BD)) is shown. Compared with the five models, the adsorption model of Cd(ATPA(4,4'-BD)) is the Langmuir single molecule adsorption model, with a specific surface area of 7.4591 m² / g and a pore volume of 0.245.
[0038] Example 7 In this example, the Cd(ATPA(4,4'-BD)) crystal material prepared in Example 1 was subjected to carbon dioxide, ethane, acetylene, ethylene, propane, and propylene adsorption experiments. The six substances in Table 1 were used and their loading amounts were compared.
[0039] Test method: Soak the sample in a methanol solution for three days, change the solution once a day, and place it in a 60°C oven for 8 hours to complete the activation of the sample. The activated sample enters the gas adsorption device.
[0040] As shown in Table 1, acetylene has the best adsorption capacity, while propane has the worst adsorption capacity, with a difference of 15.9 cm -3 / g. From the degree of electron dispersion of the six substances, it is found that the more concentrated the electrons are, the greater the adsorption amount is. Propane has no covalent bonds and has the most carbon atoms, so it has the largest spatial extension; on the other hand, acetylene contains only two carbon atoms and two hydrogen atoms, and there is a carbon-carbon triple bond, and the electron density is concentrated on the triple bond. Pyridine diaryl olefins containing perfluorinated rings have six CF bonds, which have relatively strong intermolecular forces on molecules with relatively concentrated electrons. Whether it is the instantaneous dipole effect or the polarization force of the CF bond, a large number of electron-rich molecules will be adsorbed.
[0041] Table 1 Adsorption of six gases by Cd(ATPA(4,4'-BD)) Substance name Adsorption capacity (cm3 / g) carbon dioxide 39.24 Ethane 36.64 Propane 36.10 Propylene 40.76 Acetylene 52.01 Ethylene 40.75 Example 8 This embodiment is a krypton gas adsorption experiment performed on different crystal materials.
[0042] Test method: Soak the sample in a methanol solution for three days, change the solution once a day, and place it in a 60°C oven for 8 hours to complete the activation of the sample. The activated sample enters the gas adsorption device. As shown in Table 2, the adsorption of krypton by the three crystals of Cd(ATPA(4,4'-BD)), Cd(NPA(4,4'-BD)), and Cd(TPA(4,4'-BD)) decreased by 10-30 cm-1 compared with the previous adsorbents. -3 / g, and Cd(ATPA(4,4'-BD)) has the best adsorption effect. At the same time, it is proved to a certain extent that ammonia has a better adsorption effect on rare gases.
[0043] Table 2 Adsorption of krypton by Cd(ATPA(4,4'-BD)), Cd(NPA(4,4'-BD)), and Cd(TPA(4,4'-BD)) Example 9 This embodiment is an experiment for separation and purification of krypton separation compounds when the krypton gas concentration is low.
[0044] Test method: Soak the sample in a methanol solution for three days, change the solution once a day, and place it in a 60°C oven for 8 hours to complete the activation of the sample. The activated sample enters the gas adsorption device.
[0045] The krypton content in the air is relatively small, and low-concentration krypton gas can achieve ideal experimental results. Therefore, we use low-concentration krypton gas experiments as shown in Table 3, and the flow rate of the experimental design is still 3 mL / min. Fig. 9As shown in the figure, the retention time of krypton is 9.5 minutes, which is consistent with the high concentration of krypton and xenon gas penetration structure. The experimental results show that for low concentrations of krypton, oxygen, carbon dioxide and nitrogen, the main gases in the air, have little effect on the separation effect of krypton.
[0046] Table 3 Low concentration krypton gas Gas Name Gas concentration Nitrogen margin oxygen 20.9%mol / mol carbon dioxide 0.0309%mol / mol Kr 40.1*10-6mol / mol Example 10 In this example, the Cd(ATPA(4,4'-BD)) crystal material prepared in Example 1 was tested by scanning electron microscopy.
[0047] like Fig.10 The SEM image of Cd(ATPA(4,4'-BD)) is shown. From the general outline of the crystal, it can be seen that it is a long, rod-shaped crystal with clear layers. The macroscopic length of the crystal can reach 5 mm-8 mm, and the edges and corners can be clearly seen. The SEM image is consistent with the macroscopic description and the single crystal structure description. At the same time, the uniform and transparent crystal body also indicates the phase purity and strength of the crystal.
[0048] Although the description of the present invention has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims in view of the prior art by reference to the appended claims, thereby effectively covering the intended scope of the present invention. In addition, the above description of the present invention is based on the embodiments foreseeable by the inventor, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that have not yet been foreseen may still represent equivalent changes to the present invention.
Claims
1. A krypton gas separation compound, characterized in that: The krypton gas separation compound is Cd(ATPA(4,4'-BD)); the asymmetric unit of which comprises a crystallographically independent divalent Cd ion, a 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and a 2-amino-terephthalic acid anion.
2. The krypton gas separation compound according to claim 1, characterized in that The krypton gas separation compound crystallizes in the monoclinic system with a space group of P21 / c.
3. The krypton gas separation compound according to claim 1, characterized in that: The coordination mode of the 2-amino-terephthalate anion is bidentate bridging μ2-ƞ1:ƞ1.
4. The krypton gas separation compound according to claim 1, characterized in that The structure of the 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane is arranged in a cis-parallel conformation, and the distance between the two active carbon atoms is 4.089 Å.
5. The krypton gas separation compound according to claim 1, characterized in that: The krypton gas separation compound is a 3-node 5-c net connection network, and its topological symbol is {3^3.4^3.5^4}.
6. The method for preparing the krypton gas separation compound according to claim 1, characterized in that: The following steps are involved: 2-Amino-terephthalic acid, 1,2-bis[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and Cd(NO3)2·4H2O were added to a mixed solution containing dimethylformamide, methanol and H2O, heated at 80°C for 72 h, filtered and washed to obtain a krypton gas separation compound.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the 2-amino-terephthalic acid, 1,2-di[2-methyl-3-thienyl-5-pyridyl]perfluorocyclopentane and Cd(NO3)2·4H2O is 1:1:
1.
8. The preparation method according to claim 6, characterized in that: In the mixed solution, the volume ratio of dimethylformamide, methanol and H2O is 3:1:
1.
9. The preparation method according to claim 6, characterized in that: The washing step comprises repeatedly washing with dimethylformamide and ethanol for 3 times.
10. Use of the krypton gas separation compound according to claim 1 in separating and purifying industrial waste gas and nuclear waste gas rich in krypton gas.
Citation Information
Cited By
Diaryl alkene hydrogen bond organic framework single crystal as well as synthesis method and application thereof
CN119775587A
